1993
DOI: 10.1063/1.858877
|View full text |Cite
|
Sign up to set email alerts
|

An update on the intermittency exponent in turbulence

Abstract: The issue of experimental determination of the intermittency exponent μ, is revisited and it is shown that the ‘‘best’’ estimate for it is 0.25±0.05. This ‘‘best’’ estimate is obtained from recent atmospheric data, and is based on several different techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
116
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 15 publications
24
116
0
1
Order By: Relevance
“…In the literature, researchers have reported µ ranging from 0.18 to 0.7. 10,11 In the case of atmospheric data, the 'best' direct estimate is 0.25±0.05 10 and our indirect magnitude cumulant analysis-based result is in agreement with it.…”
Section: A Analysis Of Hot Wire Measurementssupporting
confidence: 78%
See 2 more Smart Citations
“…In the literature, researchers have reported µ ranging from 0.18 to 0.7. 10,11 In the case of atmospheric data, the 'best' direct estimate is 0.25±0.05 10 and our indirect magnitude cumulant analysis-based result is in agreement with it.…”
Section: A Analysis Of Hot Wire Measurementssupporting
confidence: 78%
“…In this respect, several alternatives (e.g., second-order integral moment, two-point correlation function, spectral density) are available in the literature. [9][10][11] Recently, Cleve et al 12 showed that among various direct approaches, the two-point correlation function ε(x + r)ε(x) of the energy dissipation field provides the most reliable estimates of µ. In this case, one can write ε(x + r)ε(x) ∼ r −µ…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not surprising that numerous studies have been conducted over the past decades for the multiscale characterizations of the ABL wind fields. Diverse methodologies with varying degrees of complexities, ranging from the traditional spectral methods [4][5][6][7][8] to the new-generation multifractal approaches [9][10][11][12][13][14], have been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…This means that while the β model is not valid quantitatively, it remains valid qualitatively. For experimental works on dissipation correlation and intermittency, see [53][54][55] and more recent [56][57][58][59][60][61].…”
Section: Forced Turbulencementioning
confidence: 99%